Enhancing the Journal - Keith A Sharkey (Canadian Journal of Gastroenterology)
The Canadian Journal of Gastroenterology continues to grow in strength as a national journal of importance to gastroenterologists and hepatologists. As the official journal of both the Canadian Association of Gastroenterolgy and the Canadian Association for the Study of the Liver, it also serves as an important tool for the dissemination of guidelines and standards for the entire medical community in Canada. We should be proud of these accomplishments. But one also needs to ask, can the Journal be better? Is there something more that can be achieved? Some would say the status quo is fine. But realistically, we regularly look to the journals of our sister associations in the United States and the United Kingdom - Gastroenterology, Hepatology and Gut - for the latest and best in our field. So, I would argue, we can achieve more and make the Journal better.